An Update on Clinical and Pathogenic Spectra of Leishmaniasis - Angamuthu Selvapandiyan; Shital Shital; Diya A’gitok Sangma; Manju Jain; Nadira Karunaweera; Nirmal K. Ganguly (Expert Reviews in Molecular Medicine)
Leishmaniasis, classified as a neglected tropical disease, exerts its impact on millions globally. Its clinical spectrum encompasses diverse forms, from benign self-resolving skin lesions (cutaneous leishmaniasis) to life-threatening visceral infections (visceral leishmaniasis or kala-azar). This review aims to comprehensively explore the spectrum of the disease as an outcome of often-overlooked parasite variants. Additionally, it addresses the emerging challenges faced in the pursuit towards disease elimination. The evolving landscape of leishmaniasis demands the development of molecular surveillance tools to detect the heterogeneous parasite strains that contribute to the emergence of new endemic foci. Such surveillance poses formidable challenges to current elimination strategies. As the disease landscape continues to evolve, understanding the molecular intricacies of causative parasite strains becomes paramount. This knowledge not only aids the understanding of the basis of emerging/shifting endemic areas but also facilitates the search for and the design of targeted interventions. In this context, this review will navigate through the dynamic terrain of leishmaniasis, the various causative species of Leishmania parasites emphasising the urgency for the development of robust surveillance mechanisms and innovative approaches to confront the evolving challenges in our quest for global disease elimination.